Statactivism: Forms of action between disclosure and affirmation - Bruno, Isabelle; Didier, Emmanuel; Vitale, Tommaso (PARTECIPAZIONE E CONFLITTO, 2014)
This article introduces the special issue on statactivism, a particular form of action within the repertoire used by contemporary social movements: the mobilization of statistics. Traditionally, statistics has been used by the worker movement within the class conflicts. But in the current configuration of state restructuring, new accumulation regimes, and changes in work organization in capitalists societies, the activist use of statistics is moving. This first article seeks to show the use of statistics and quantification in contentious performances connected with state restructuring, main transformations of the varieties of capitalisms, and changes in work organization regimes. The double role of statistics in representing as well as criticizing reality is considered. After showing how important statistical tools are in producing a shared reading of reality, we will discuss the two main dimensions of statactivism – disclosure and affirmation. In other words, we will see the role of stat-activists in denouncing a certain state of reality, and then the efforts to use statistics in creating equivalency among disparate conditions and in cementing emerging social categories. Finally, we present the main contributions of the various research papers in this special issue regarding the use of statistics as a form of action within a larger repertoire of contentious action. Six empirical papers focus on statactivism against the penal machinery in the early 1970s (Grégory Salle), on the mobilisation on the price index in Guadalupe in 2009 (Boris Samuel), and in Argentina in 2007 (Celia Lury and Ana Gross), on the mobilisations of experts to consolidate a link between working conditions and health issues (Marion Gilles), on the production of activity data for disability policy in France (Pierre-Yves Baudot), and on the use of statistics in social mobilizations for gender equality (Eugenia De Rosa). Alain Desrosières wrote the last paper, coping with mobilizations proposing innovations in the way of measuring inflation, unemployment, poverty, GDP, and climate change. This special issue is dedicated to him, in order to honor his everlasting intellectual legacy